Characterization and efficient production of an α‐agarase from marine bacterium Catenovulum maritimum STB14. Issue 1 (23rd December 2022) - You, Yuxian; Xie, Wenyan; Li, Caiming; Gu, Zhengbiao; Ban, Xiaofeng; Zhang, Feng; Li, Zhaofeng
Abstract: Agarases are enzymes that degrade agar and agarose to produce agar oligosaccharides with multiple functional activities. Compared with β‐agarases, the natural source of α‐agarases is limited, which severely restricts the industrial application of α‐agarases. Here, we cloned and heterologously expressed an α‐agarase belonging to glycoside hydrolase family 96 named Cm‐AGA from the marine bacterium Catenovulum maritimum STB14. The production conditions of recombinant Cm‐AGA were optimized as: taking Terrific Broth (TB) (pH 6.5) with 5 g/L of fructose and 24 g/L of yeast extract H07014 as the fermentation medium, after culturing at 37°C for 2 h, isopropyl‐β‐ d ‐thiogalactoside was added with a final concentration of 0.01 mM to induce for 44 h. The obtained enzyme activity was 13.81 U/ml and was about 6.6 times the initial activity. The specific activity of recombinant Cm‐AGA was 206.1 U/mg, the optimum temperature and pH were 35°C and 8.0, respectively, and the enzyme activity could be activated by Mn 2+ and Ca 2+ . The hydrolysis product results showed that Cm‐AGA is the first reported α‐agarase with agarobiose (A2) and agarotetraose (A4) as the dominant products, suggesting the great potential of Cm‐AGA in the efficient production of agaro‐oligosaccharides with a low degree of polymerization. Abstract : This article cloned and heterologously expressed a novel α‐agarase (Cm‐AGA) from marine bacteria with a specific activity of 206.1 U/mg. The crude enzyme activity of recombinant Cm‐AGA was significantly increased through fermentation strategy optimization. The catalytic properties and hydrolysis products of recombinant Cm‐AGA were characterized as well.